Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations steeped in salt water, soaped and then brought to the boil for a few minutes. They will "iron" beautifully if smoothed upon a flat surface to dry. Little dress accessories, such as modesty vests, cuffs and collars are best done by oneself, and can then be always fresh and spotless. It is in such matters that a girl shows her innate refinement, a quality that appeals strongly to the opposite sex. Those tight-fitting little felt hats, too, should go to the cleaners occasionally; it is amazing how quickly they pick up grime. So do furs, which are capable of holding the germs of past colds and coughs to re-infect their wearer again and again. Furs, thick woollens and outdoor garments will benefit by an occasional clean with the electric vacuum cleaner. It is really amazing how much dust collects in heavy clothing. Pockets and hems and cuffs all need special attention for this reason. A pair of well-polished shoes gives the finishing touch to a dainty toilet. First remove every trace of dust or dry mud with a stiff brush. Should the shoes be badly caked with wet mud, it is a good plan to scrub them over a pail of water, being careful not to wet the insides. After thorough drying, rub in a good shoe polish and finish to a high gloss with a soft rag. Girls often worry because their figures are "lumpy." If you are not yet twenty you will, I am sure, find yourself getting more shapely as you get older. Meanwhile do not eat too many sweets and cream cakes, and eat fruit and salads in place of them. So, heads up, shoulders back, grace and dignity, please! You know by this that you are perfectly charming, having observed all the simple rules of health and cleanliness. Complete your toilet in the privacy of your own room; prinking in public is the essence of bad taste, and self-consciousness is a miserable state of mind. Above all, do not commit the error of "making-up" in public. Do your wholesome best to be beautiful — and then forget it! 20 177/5/8/4